La lectura dialógica como medio para la mejora de la comprensión lectora - Raúl Gutiérrez Fresneda (Investigaciones Sobre Lectura)
In our society, written communication has a special significance, being an essential reading for access to information and for school success. Children acquire learning to read from the earliest ages from the relationship with the people around them. Dialogic learning is in the context of theories that emphasize interaction and dialogue as sources of learning so that the meaning, understanding and learning are enhanced through interactions that are established through a text. The purpose of this study was to analyze whether through learning programs that integrate dialogic reading along with the usual practices focused on teaching reading improved reading skills are acquired. A quasi-experimental comparison group design with pretest and posttest measures was used. In the study 120 students participated aged between 8 and 9 years. The results weigh the potential value of the program and support the development of teaching models that integrate dialogic reading practices in classroom dynamics as it facilitates the learning of reading comprehension.